No Minor Accomplishment : The Revival of New Jersey Professional Baseball - Golon, Bob (Book collections on Project MUSE., 2008)
In No Minor Accomplishment, sports historian and New Jersey native Bob Golon tells the story of the state's baseball scene since the Trenton Thunder arrived in 1994. Drawing on interviews with team owners and employees, industry executives and fans, Golon goes behind the scenes to show how maintaining a minor league ball club can be a risky business venture. Stadiums cost millions to build and a team full of talented players does not immediately guarantee success. Instead, each of the eight Minor League and independent professional teams in the state must tailor itself to the communities in which it is situated.